The Relationship of Knowledge About Mastalgia With Anxiety Levels of Female Adolescents Aged 15-17 Years Who Experienced Mastalgia - nur azizah; wiwik muhidayati; rina utami; Tri Wulandari (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Mastalgia is pain and dilation of the mammary glands before menstruation that was caused by edema and a relative increase in estrogen levels. The purpose of this research is to analyze the relationship of knowledge between adolescent knowledge and the level of anxiety of adolescents who experienced Mastalgia. This research method is correlational analytic with cross sectional approach. The population was an entire adolescent’s female in July 2013 in Sumbertlaseh Village, Dander Subdistrict, Bojonegoro Regency as many as 253 sample students, and as many as 84 respondents. The sampling technique used purposive sampling: collecting data using a questionnaire, then through the process of editing, coding, scoring, and tabulating. While the results are presented in the form of images, tables and narrations. Then edited, coded, scored, tabulated and faced with Chi Square test. α <0.05), the research results are presented in the form of Figures, tables and narratives. Both variables were tested for significance by using cross table data analysis with a value of: 0.05 with a value obtained a value of 27.5> 0.05 so Ho is rejected, which means there is a relationship between knowledge about mastalgia and anxiety in adolescent female aged 15-17 years who experienced mastalgia at the Abu Dharin Islamic Boarding School, Sumberlaseh Village, Bojonegoro Regency. The conclusion of this study is that there is a relationship between knowledge about mastalgia and anxiety for adolescents aged 15-17 years who experience mastalgia at Boarding School Abu Dharin.